Traveling Traditions: Nineteenth-Century Cultural Concepts and Transatlantic Intellectual Networks - Redling, Erik (Buchreihe der Anglia, 2016)
This study seeks to fill a major gap in the fields of Nineteenth-Century American and British Studies by examining how nineteenth-century intellectuals shape and re-shape aesthetic traditions across the Atlantic Ocean. The study explores the roles of salient traveling concepts, such as realism, translation, the picturesque, and imagination, and traces their at times surprising paths within ever-widening transnational intellectual networks.
Keywords: Konferenzschrift -- 2014 -- Halle (Saale); Geschichte 1800-1900; Kulturaustausch; Geistesleben; USA; Großbritannien